Strategic Silence: Withholding Certification Status as a Hypocrisy Avoidance Tactic - Carlos, W. Chad; Lewis, Ben W. (Administrative Science Quarterly, 2018)
We examine why organizations that obtain prominent certifications may at times elect not to publicize them. Drawing on the impression management literature, we argue and show that concerns about being perceived as hypocritical may cause organizations to strategically withhold their certification status. Using a longitudinal panel of corporations that were members of the Dow Jones Sustainability Index, a prominent environmental certification, we show that in the face of reputational threats, organizations are less likely to publicize their certification status when the threat appears to directly contradict the claims implied by the certification. Our findings suggest that the threat of hypocrisy is amplified for firms with stronger reputations in the same domain as the certification and when audience members better understand and value the certification. Our findings delineate new boundary conditions under which firms will make prosocial claims and inspire reconsideration of long-held assumptions about the process of decoupling the implementation and communication of socially valued practices. This study also provides insights for scholars of nonmarket strategy on how corporations strategically communicate with external constituents about their sustainability initiatives.